Experimental and Numerical Simulation Study of Polymer and Surfactant Adsorptions during Chemical EOR Flooding - HAMID ALI, MOHAMED ALI (2013)
Adsorption of the chemicals (e.g., polymers, surfactants, and alkaline) used in chemical EOR (CEOR) onto formation rock surfaces is of big concern because it represents loss of the chemicals from the solution, and consequently, a net reduction in the chemical slug. Therefore, the efficiency of chemical flooding in the reservoir will be significantly affected not only by technical but also economical aspects. Also, the most of the adsorption models available in the literature for the CEOR screening and simulation studies do not account for the combined effects of various parameters such as temperature, pH, salinity, and the molecular weights that may significantly affect adsorption.